2012
DOI: 10.1016/j.jval.2012.08.2126
|View full text |Cite
|
Sign up to set email alerts
|

PCN86 Cost-Effectiveness Analysis of Abiraterone for the Treatment of Advanced Prostate Cancer Under the Brazilian Private Health Care System

Abstract: utilities for pazopanib and placebo were from PALETTE. Lacking a connected evidence network, estimates of relative effectiveness for trabectedin and ifosfamide were from an unadjusted indirect treatment comparison vs. pazopanib. Costs were from NHS reference costs and other published sources. RESULTS: Compared with placebo, pazopanib is estimated to increase QALYs by 0.130 and costs by £8,072; the incremental cost effectiveness ratio (ICER) for pazopanib vs. placebo is estimated to be £63k/QALY gained. For mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…This study found that, in the Brazilian private health system, abiraterone was both more effective at increasing QALYs and providing lower costs as compared to cabazitaxel. ( 21 ) The study by Pereira et al, ( 21 ) is different from ours. First, they assessed the treatment for castration-refractory patients previously treated with docetaxel, while we assessed the treatment for newly diagnosed castration-sensitive disease (median duration of abiraterone therapy 6 months versus 34 months, respectively).…”
Section: Discussioncontrasting
confidence: 70%
“…This study found that, in the Brazilian private health system, abiraterone was both more effective at increasing QALYs and providing lower costs as compared to cabazitaxel. ( 21 ) The study by Pereira et al, ( 21 ) is different from ours. First, they assessed the treatment for castration-refractory patients previously treated with docetaxel, while we assessed the treatment for newly diagnosed castration-sensitive disease (median duration of abiraterone therapy 6 months versus 34 months, respectively).…”
Section: Discussioncontrasting
confidence: 70%
“…Dados sobre ganho de QALY e anos de vida em outros modelos de custo-efetividade da abiraterona estão disponíveis na literatura internacional. Os resultados desses estudos em termos de QALY e anos de vida ganhos (abiraterona ver- sus tratamento padrão) variam amplamente, havendo dois estudos cujos resultados de 0,06 e 0,27 foram menos favoráveis que o do presente trabalho (Pereira et al, 2012;Zhong et al, 2013); um estudo chegou a 0,30, número quase idêntico ao aqui estimado (Chopra et al, 2012); e dois trabalhos encontraram valores de 0,47 (Marin Piva et al, 2016;Persson et al, 2012), maiores do que os apresentados na presente avaliação. Porém, conhecendo-se o custo do medicamento no Brasil, mesmo que tivéssemos encontrado os valores mais favoráveis da literatura (Marin Piva et al, 2016), os resultados para um limiar de três vezes o PIB per capita ainda não seriam custo-efetivos.…”
Section: Discussionunclassified